2001
DOI: 10.1017/s0048577201981867
|View full text |Cite
|
Sign up to set email alerts
|

Neural sources involved in auditory target detection and novelty processing: An event-related fMRI study

Abstract: We used event-related functional magnetic resonance imaging (erfMRI) techniques to examine the cerebral sites involved with target detection and novelty processing of auditory stimuli. Consistent with the results from a recent erfMRI study in the visual modality, target processing was associated with activation bilaterally in the anterior superior temporal gyrus, inferior and middle frontal gyrus, inferior and superior parietal lobules, anterior and posterior cingulate, thalamus, caudate, and the amygdala/hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
123
3
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 8 publications
24
123
3
2
Order By: Relevance
“…This extensive network of brain regions associated with target detection may be similar to the attention network discussed by Mesalum (Mesulam, 1990;Mesulam, 2000). Others have suggested that processing salient stimuli is associated with an 'reflexive' or 'automatic' orienting process that is reliably activates an extensive neural network despite the low probability that all activated brain regions are required for successful task performance (Kiehl et al, 2001a;Kiehl et al, 2001b;Kiehl & Liddle, 2003;Kiehl et al, 2005).Also consistent with study hypotheses, target detection was associated with greater hemodynamic activity during the single-tone condition compared to the two-tone condition in bilateral middle temporal gyrus, inferior frontal and middle prefrontal gyri. These findings are consistent with electrophysiological and magnetoencephalogram studies of single-, two-and three-tone oddball tasks.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…This extensive network of brain regions associated with target detection may be similar to the attention network discussed by Mesalum (Mesulam, 1990;Mesulam, 2000). Others have suggested that processing salient stimuli is associated with an 'reflexive' or 'automatic' orienting process that is reliably activates an extensive neural network despite the low probability that all activated brain regions are required for successful task performance (Kiehl et al, 2001a;Kiehl et al, 2001b;Kiehl & Liddle, 2003;Kiehl et al, 2005).Also consistent with study hypotheses, target detection was associated with greater hemodynamic activity during the single-tone condition compared to the two-tone condition in bilateral middle temporal gyrus, inferior frontal and middle prefrontal gyri. These findings are consistent with electrophysiological and magnetoencephalogram studies of single-, two-and three-tone oddball tasks.…”
supporting
confidence: 72%
“…This study illustrates that a large ensemble of brain regions, known to be involved in target detection during three-tone auditory oddball tasks (Kiehl et al, 2001a;Kiehl et al, 2001b;Kiehl & Liddle, 2003), also are engaged by target detection in single-and two-tone auditory oddball paradigms. Target detection in both single-tone and two-tone fMRI auditory oddball tasks elicited significant hemodynamic activity in all 34 a priori-defined regions of interest (ROIs).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Specifically, attentional processes that involve sustained, and possibly selective, attention (Coull et al, 1996), switching from task-relevant local to global targets (Fink et al, 1996;Lamb et al, 1989), voluntary attentional control (Hopfinger et al, 2000), and the distinction between taskirrelevant and task-relevant events (Downar et al, 2001;Kiehl et al, 2001;McCarthy et al, 1997) support the view that this area is critical for the extraction and selection of task-relevant information. Moreover, this area has been implicated in inhibitory control in a number of different paradigms (Garavan et al, 1999;Menon et al, 2001;Rubia et al, 2001b;Steel et al, 2001;Doricchi et al, 1997), that is, the allocation of resources to a response that has to compete with a highly overlearned and potentially habitual behavior.…”
Section: Decision-making and Errors In Schizophreniamentioning
confidence: 94%